Real-world federated learning in radiology: hurdles to overcome and benefits to gain - Bujotzek, Markus; Akünal, Ünal; Denner, Stefan; Neher, Peter; Zenk, Maximilian; Frodl, Eric; Jaiswal, Astha; Kim, Moon; Krekiehn, Nicolai R.; Nickel, Manuel; Ruppel, Richard; Both, Marcus; et al. (Journal of the American Medical Informatics Association, 2025)
OBJECTIVE: Federated Learning (FL) enables collaborative model training while keeping data locally. Currently, most FL studies in radiology are conducted in simulated environments due to numerous hurdles impeding its translation into practice. The few existing real-world FL initiatives rarely communicate specific measures taken to overcome these hurdles. To bridge this significant knowledge gap, we propose a comprehensive guide for real-world FL in radiology. Minding efforts to implement real-world FL, there is a lack of comprehensive assessments comparing FL to less complex alternatives in challenging real-world settings, which we address through extensive benchmarking. - MATERIALS AND METHODS: We developed our own FL infrastructure within the German Radiological Cooperative Network (RACOON) and demonstrated its functionality by training FL models on lung pathology segmentation tasks across six university hospitals. Insights gained while establishing our FL initiative and running the extensive benchmark experiments were compiled and categorized into the guide. - RESULTS: The proposed guide outlines essential steps, identified hurdles, and implemented solutions for establishing successful FL initiatives conducting real-world experiments. Our experimental results prove the practical relevance of our guide and show that FL outperforms less complex alternatives in all evaluation scenarios. - DISCUSSION AND CONCLUSION: Our findings justify the efforts required to translate FL into real-world applications by demonstrating advantageous performance over alternative approaches. Additionally, they emphasize the importance of strategic organization, robust management of distributed data and infrastructure in real-world settings. With the proposed guide, we are aiming to aid future FL researchers in circumventing pitfalls and accelerating translation of FL into radiological applications.
Online veröffentlicht: 25. Oktober 2024
Gesehen am 13.08.2025